The use of experts and their judgments in nursing research: an overview - JC Bruce (AOSIS, 2008)
Experts and their judgments are widely used in the fields of research, education, health care, law, commerce and technology. Expert judgment is known for its subjectivity and its potential for bias, which brings into question the accuracy and authenticity of judgmental data. At the same time there is acknowledgment of the valued contribution of judgmental data towards valid inferences in research and education. Maximizing the use of experts and their judgments has therefore become an endeavour of educationists and researchers alike.